The safety of colorectal cancer surgery during the COVID-19: a systematic review and meta-analysis - Wang, Qiuxiang; Wu, Ruike; Wang, Juan; Li, Yilin; Xiong, Qin; Xie, Fengjiao; Feng, Peimin (Frontiers in Oncology, 2023)
Background The ongoing coronavirus disease 2019 (COVID-19) pandemic has placed unprecedented pressure on the healthcare systems. This study evaluated the safety of colorectal cancer (CRC) surgery during the COVID-19 pandemic. Methods A systematic review and meta-analysis were performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (PROSPERO ID: CRD 42022327968). Relevant articles were systematically searched in the PubMed, Embase, Web of Science, and Cochrane databases. The postoperative complications, anastomotic leakage, postoperative mortality, 30-day readmission, tumor stage, total hospitalization, postoperative hospitalization, preoperative waiting, operation time, and hospitalization in the intensive care unit (ICU) were compared between the pre-pandemic and during the COVID-19 pandemic periods. Results Among the identified 561 articles, 12 met the inclusion criteria. The data indicated that preoperative waiting time related to CRC surgery was higher during the COVID-19 pandemic (MD, 0.99; 95%CI, 0.71–1.28; p < 0.00001). A similar trend was observed for the total operative time (MD, 25.07; 95%CI, 11.14–39.00; p =0.0004), and on T4 tumor stage during the pandemic (OR, 1.77; 95%CI, 1.22–2.59; p=0.003). However, there was no difference in the postoperative complications, postoperative 90-day mortality, anastomotic leakage, and 30-day readmission times between pre-COVID-19 pandemic and during the COVID-19 pandemic periods. Furthermore, there was no difference in the total hospitalization time, postoperative hospitalization time, and hospitalization time in ICU related to CRC surgery before and during the COVID-19 pandemic. Conclusion The COVID-19 pandemic did not affect the safety of CRC surgery. The operation of CRC during the COVID-19 pandemic did not increase postoperative complications, postoperative 90-day mortality, anastomotic leakage, 30-day readmission, the total hospitalization time, postoperative hospitalization time, and postoperative ICU hospitalization time. However, the operation of CRC during COVID-19 pandemic increased T4 of tumor stage during the COVID-19 pandemic. Additionally, the preoperative waiting and operation times were longer during the COVID-19 pandemic. This provides a reference for making CRC surgical strategy in the future. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022327968.